Novel RNAs Identified From an In-Depth Analysis of the Transcriptome of Human Chromosomes 21 and 22 - Kampa, Dione; Cheng, Jill; Kapranov, Philipp; Yamanaka, Mark; Brubaker, Shane; Cawley, Simon; Drenkow, Jorg; Piccolboni, Antonio; Bekiranov, Stefan; Helt, Gregg; Tammana, Hari; Gingeras, Thomas R. (Genome Research, 2004)
In this report, we have achieved a richer view of the transcriptome for Chromosomes 21 and 22 by using high-density oligonucleotide arrays on cytosolic poly(A)+ RNA. Conservatively, only 31.4% of the observed transcribed nucleotides correspond to well-annotated genes, whereas an additional 4.8% and 14.7% correspond to mRNAs and ESTs, respectively. Approximately 85% of the known exons were detected, and up to 21% of known genes have only a single isoform based on exon-skipping alternative expression. Overall, the expression of the well-characterized exons falls predominately into two categories, uniquely or ubiquitously expressed with an identifiable proportion of antisense transcripts. The remaining observed transcription (49.0%) was outside of any known annotation. These novel transcripts appear to be more cell-line-specific and have lower and less variation in expression than the well-characterized genes. Novel transcripts were further characterized based on their distance to annotations, transcript size, coding capacity, and identification as antisense to intronic sequences. By RT-PCR, 126 novel transcripts were independently verified, resulting in a 65% verification rate. These observations strongly support the argument for a re-evaluation of the total number of human genes and an alternative term for “gene” to encompass these growing, novel classes of RNA transcripts in the human genome.